Exploring natural allies: Survey and identification of larval parasitoids of the American grape berry moth, Paralobesia viteana (Lepidoptera: Tortricidae) in northwestern Pennsylvania - Jesús H. Gómez-Llano; Neetu Khanal; Flor E. Acevedo (PLoS ONE, 2025)
The American grape berry moth (GBM), Paralobesia viteana (Clemens) (Lepidoptera: Tortricidae) is an economically important pest of grapes. The larvae of this insect burrow inside the fruit upon hatching, consuming, and contaminating grapes and clusters. Current GBM management relies on pesticide applications, which do not offer complete protection due to the cryptic behavior of the larvae and asynchrony in egg-laying, highlighting the need to develop new management strategies. In this study, we identified GBM larval parasitoids in commercial vineyards and quantified their parasitism rates. Parasitoid samplings were conducted biweekly in six conventionally managed ‘Concord’ vineyards in Erie County, Pennsylvania, during the 2023 and 2024 growing seasons. GBM-infested samples were monitored daily to track the emergence of both parasitoids and GBM, enabling the calculation of parasitism rates. We identified eight parasitoid species: Enytus obliteratus (Cresson) (Hymenoptera: Ichneumonidae), Campoplex tortricidis (Cushman) (Hymenoptera: Ichneumonidae), Scambus spp. Hartig (Hymenoptera: Ichneumonidae), Glypta cf. depressa Dasch, Glypta cf. ohioensis Dasch, and Glypta cf. ignota Dasch (Hymenoptera: Ichneumonidae); Bracon variabilis (Provancher) (Hymenoptera: Braconidae), and Goniozus fratellus Evans (Hymenoptera: Bethylidae) preying on GBM larvae. From these, B. variabilis, E. obliteratus, and G. fratellus were the most abundant. We also designed a graphic taxonomic key to facilitate the identification of these species. The parasitoid abundance differed over the growing season but was greatest in early August, reaching parasitism rates of up to 39% and 52.1% in 2023 and 2024, respectively. Our results demonstrate that GBM has several larval parasitoids that help reduce its populations in commercial vineyards. This research represents a first step toward our understanding of the GBM native natural enemies present in the Lake Erie Region and their potential use in pest management programs.